A model for the development and implementation of a national plan for the optimal management of early spondyloarthritis: the Esperanza Program. Issue 5 (17th January 2011) - Muñoz-Fernández, Santiago; Carmona, Loreto; Collantes, Eduardo; Mulero, Juan; García-Yébenes, M Jesús; de Miguel, Eugenio; Almodovar, Raquel; Fernández-Carballido, Cristina; Llorente, José Francisco García; Gobbo, Milena; ,
Abstract : Objectives: To evaluate the performance of a healthcare programme in early spondyloarthritis (SpA). Methods: Based on previous analyses and expectations of a nominal group, the following were set: (1) minimum standards to create early SpA units; (2) standard operating procedures; and (3) eight performance indicators that can be measured in real time using a web-based platform. Results: At the end of the evaluation of the programme the expected level of performance was achieved in three of the indicators: 'referral reliability' (standard (S) >50%, real value (RV) 92%), 'accessibility' (S >90%, RV=91%) and 'duration of first visit' (S >50%, RV=53%). The performance in the remaining indicators was inferior: 'success of referral criteria' (S >50%, RV=28%), 'clinical reports issued' (S >90%, RV=25%), 'feedback guarantee' (S >85%, RV=2%), 'missing data' (S <10%, RV=24%) and 'frequency of review' (S >90%, RV=84%). Explanations for the low performance are provided. Conclusions: It is possible to implement a large-scale programme that is measurable.